Morfogênese do relevo de chapadas no divisor hidrográfico entre as bacias do Tocantins/Araguaia com o São Francisco - Thaís Aparecida Silva (2018)
The relief is the result from interaction between endogenous forces that create shapes and exogenous forces that promote wearing down of such shapes. In this sense, rivers act as erosive agents, one of the most significant mechanisms in sculpting the continental relief. The goal of this research was to understand the morphogenesis of the interfluve between Tocantins basin and São Francisco basin, an area rich in chapadas landforms. The initial hypothesis is that the Tocantins Basin (subbasin of Paranã River) is more aggressive, we have erosive terms, than the São Francisco. Thus, the step in the relief that configures the hydrographic divisor tends to retreat in the direction of west to east. The result of this lateral retreat of the cliffs are the residual reliefs that demarcate old fronts of the chapadas. This research was structured in three stages: (i) gathering of materials and literature on the study area and the subject (ii) technical-operational proceedings, developed through remote sensing and geoprocessing data (generation of Digital Terrain Model; regional topographic profiles; geomorphological segmentation; residual relief mapping; longitudinal profile of main channels; Hack index calculation), (iii) in field proceedings, through observance and photographic register. The results show that the Paranã subbasin is affected by structure, which yield the channels greater energy. As for the erosive power of tributaries of Paranã river that drain the interfluve, these are energetically favored due to the upkeep of an elevated hydraulic gradient. In the São Francisco basin the tributaries that drain the interfluve display similar or lesser energy than the Parana tributaries. Regarding fluvial incision São Francisco tributaries display distinct behavior: the incision aggressiveness increases from north to south, due to structure and hydraulic gradient. Relating to this matter the chapadas discontinuities also increase from north to south. As for the regional relief evolution the hypothesis is that the chapadas unity used to occupy a greater area and with the development of drainage network fluvial incision was promoted, specially and more aggressively in the Paranã subbasin due to structural influence, which allowed for carbonate rocks to be reached more quickly hence contributing to the opening of Valley do Paranã. In the São Francisco basin however, the reduced structural influence north of the area and the extent of channels have culminated in slower incision, which differs from the south-center region wherein the structure, neotectonics and hydraulic gradient control the incision rate.